Ecology, seasonality and host preferences of Austrian Phlebotomus (Transphlebotomus) mascittii Grassi, 1908, populations - Kniha, Edwin; Milchram, Markus; Dvořák, Vít; Halada, Petr; Obwaller, Adelheid G; Poeppl, Wolfgang; Mooseder, Gerhard; Volf, Petr; Walochnik, Julia (Parasites & vectors, 2021)
BACKGROUND: Sand flies are principal vectors of the protozoan parasites Leishmania spp. and are widely distributed in all warmer regions of the world, including the Mediterranean parts of Europe. In Central European countries, the sand fly fauna is still under investigation. Phlebotomus mascittii, a suspected but unproven vector of Leishmania infantum, is regarded as the most widely distributed species in Europe. However, many aspects of its biology and ecology remain poorly known. The aim of this study was to provide new data on the biology and ecology of Ph. mascittii in Austria to better understand its current distribution and potential dispersal. METHODS: Sand flies were collected by CDC light traps at four localities in Austria for 11 (2018) and 15 weeks (2019) during the active sand fly season. Climatic parameters (temperature, relative humidity, barometric pressure and wind speed) were retrospectively obtained for the trapping periods. Sand flies were identified by a combined approach (morphology, DNA barcoding, MALDI-TOF protein profiling), and blood meals of engorged females were analysed by DNA sequencing and MALDI-TOF mass spectrometry. RESULTS: In total, 450 individuals of Ph. mascittii were caught. Activity was observed to start at the beginning of June and end at the end of August with peaks in mid-July at three locations and early August at one location. Increased activity was associated with relatively high temperatures and humidity. Also, more individuals were caught on nights with low barometric pressure. Analysis of five identified blood meals revealed chicken (Gallus gallus) and equine (Equus spp.) hosts. Sand fly abundance was generally associated with availability of hosts. CONCLUSION: This study reports unexpectedly high numbers of Ph. mascittii at selected Austrian localities and provides the first detailed analysis of its ecology to date. Temperature and humidity were shown to be good predictors for sand fly activity. Blood meal analyses support the assumption that Ph. mascittii feeds on mammals as well as birds. The study significantly contributes to understanding the ecology of this sand fly species in Central Europe and facilitates prospective entomological surveys.
Keywords: roční období; Horses; kur domácí; Chickens; Female; Evropa; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; retrospektivní studie; Austria; hmyz - vektory; Leishmania infantum; Seasons; Rakousko; Sequence Analysis, DNA; mužské pohlaví; Insect Vectors; sekvenční analýza DNA; zvířata; spektrometrie hmotnostní - ionizace laserem za účasti matrice; koně; ženské pohlaví; Phlebotomus; Animals; Male; Europe; Retrospective Studies; ekologie; Ecology; Psychodidae